Efficacy of electroacupuncture treatment for generalized anxiety disorder related insomnia: a study protocol for randomized controlled trial - Yao, Wang; Wang, Xi; Liu, Huanyi; Liu, Lumin; Fan, Qian; Yin, Ping; Chen, Yuelai (Frontiers in Psychiatry, 2025)
BackgroundGeneralized anxiety disorder (GAD) is a prevalent mental disorder characterized by excessive tension, worry, fear, and autonomic symptoms, which brings huge suffering to patients. Insomnia, one of the most common symptoms experienced by individuals with GAD, often exacerbates anxiety symptoms. Electroacupuncture (EA), a non-pharmacological treatment for insomnia, presents several advantages, including significant efficacy, minimal side effects, and high patient acceptance. However, there is a lack of high-quality randomized controlled trials evaluating the efficacy and safety of EA.MethodsThis study was designed as a randomized, sham-controlled clinical trial. 84 eligible patients with GAD-related insomnia will be randomly assigned to receive either three sessions of EA or sham EA weekly for 8 weeks. The primary outcome will be the change in the Pittsburgh Sleep Quality Index (PSQI) score at week 8. Hamilton Anxiety Rating Scale (HAMA), Insomnia Severity Index (ISI), sleep diary entries, actigraphy sleep assessment, 12-item Short-Form Health Survey, and weekly usage of medication will provide a thorough evaluation of sleep, anxiety, and overall living conditions.DiscussionThis study aims to evaluate the efficacy and safety of EA for treating insomnia in patients with GAD, proving EA can enhance patients’ quality of life and reduce their dependence on medications.Clinical trial registrationClinicalTrials.gov, identifier ChiCTR2400083326.